Investigation of the Physical Processes Involved in GNSS Amplitude Scintillations at High Latitude: A Case Study - Giulia D’Angelo; Mirko Piersanti; Alessio Pignalberi; Igino Coco; Paola De Michelis; Roberta Tozzi; Michael Pezzopane; Lucilla Alfonsi; Pierre Cilliers; Pietro Ubertini (Remote Sensing, 2021)
The storm onset on 7 September 2017, triggered several variations in the ionospheric electron density, causing severe phase fluctuations at polar latitudes in both hemispheres. In addition, although quite rare at high latitudes, clear amplitude scintillations were recorded by two Global Navigation Satellite System receivers during the main phase of the storm. This work attempted to investigate the physical mechanisms triggering the observed amplitude scintillations, with the aim of identifying the conditions favoring such events. We investigated the ionospheric background and other conditions that prevailed when the irregularities formed and moved, following a multi-observations approach. Specifically, we combined information from scintillation parameters and recorded by multi-constellation (GPS, GLONASS and Galileo) receivers located at Concordia station (75.10°S, 123.35°E) and SANAE IV base (71.67°S, 2.84°W), with measurements acquired by the Special Sensor Ultraviolet Spectrographic Imager on board the Defense Meteorological Satellite Program satellites, the Super Dual Auroral Radar Network, the Swarm constellation and ground-based magnetometers. Besides confirming the high degree of complexity of the ionospheric dynamics, our multi-instrument observation identified the physical conditions that likely favor the occurrence of amplitude scintillations at high latitudes. Results suggest that the necessary conditions for the observation of this type of scintillation in high-latitude regions are high levels of ionization and a strong variability of plasma dynamics. Both of these conditions are typically featured during high solar activity.